UAV-Based Engineering Reconnaissance: Strategi Arsitektur Pertahanan Dalam Mitigasi Infrastruktur Vital Pasca Bencana - Agung Prapsetyo; Ilhan Yasin; Kiki Lestari; Danny Reifan Adriansyah; Daffa Putra Handara (JURNAL TEKNIK SIPIL PERTAHANAN, 2026)
Unmanned Aerial Vehicle (UAV) or unmanned aircraft, currently the development of technology, particularly in the context of engineering reconnaissance and post-disaster critical infrastructure mitigation. Critical infrastructure is a strategic component in defense architecture that often suffers damage due to natural disasters and armed conflicts, requiring rapid, accurate, and personnel-safe damage assessment strategies. This research aims to examine the integration strategy of UAV technology in military engineering for post-disaster critical infrastructure mitigation based on defense architecture concepts. The method used in this research is a literature research method, using a descriptive qualitative approach, then analyzed the development of UAV technology, remote sensing payloads, and Artificial Intelligence in military and civil contexts. The results show that the integration of UAVs equipped with multispectral payloads, LiDAR, and swarm intelligence systems can improve infrastructure damage assessment efficiency by up to 70% compared to conventional methods, reduce personnel risks in hazardous areas, and produce high-resolution spatial data for defense reconstruction planning. The recommendations proposed include the development of UAV-based engineering reconnaissance doctrine, standardization of military drone operator training, and integration of digital twin systems for critical infrastructure vulnerability simulation in national defense architecture.